STRATEGI PENGUATAN KINERJA KARYAWAN MELALUI KEPEMIMPINAN DAN KEPUASAN KERJA PADA PT EPSON [STRATEGIC APPROACHES TO ENHANCING EMPLOYEE PERFORMANCE THROUGH LEADERSHIP AND JOB SATISFACTION AT PT EPSON] - Marlina, Henni (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to analyze strategies for strengthening employee performance through leadership and job satisfaction at PT Epson. The study used an associative quantitative approach with a survey method of 60 employees selected using a saturated sampling technique. Data were collected through a structured questionnaire and analyzed using simple linear regression and multiple linear regression, supplemented by correlation coefficients, coefficients of determination, partial t-tests, and simultaneous F-tests. The results of the study indicate that leadership and job satisfaction play a significant role in strengthening employee performance, both partially and simultaneously, with a relatively strong explanatory contribution of the variables. Simultaneously, leadership and job satisfaction provide the largest contribution to employee performance, which emphasizes the importance of integrating effective leadership and sustainable job satisfaction management. The conclusion of this study confirms that strategies for strengthening employee performance at PT Epson need to be directed at improving leadership quality and creating job satisfaction to support the achievement of optimal organizational performance.